2014
DOI: 10.1021/jp501559x
|View full text |Cite
|
Sign up to set email alerts
|

Coating Mechanisms of Single-Walled Carbon Nanotube by Linear Polyether Surfactants: Insights from Computer Simulations

Abstract: ABSTRACT.The non-covalent coating of carbon-based nanomaterials, such as carbon nanotubes, has important applications in nanotechnology and nanomedicine. The molecular modeling of this process can clarify its mechanism and provide a tool for the design of novel materials. In this paper, the coating mechanism of single-walled carbon nanotubes (SWCNT) in aqueous solutions by 1,2 -dimethoxyethane oxide (DME), 1,2 -dimethoxypropane oxide (DMP), polyethylene oxide (PEO), polypropylene oxide (PPO) pentamers, and L64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
6
16
0
Order By: Relevance
“…The reason for this is plausibly the restriction imposed on molecular motions in the PPO block by its surface attachment. Strong anchoring of PPO blocks has been a feature observed in explicit molecular simulations of the adsorption of Pluronics to CNTs. , …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The reason for this is plausibly the restriction imposed on molecular motions in the PPO block by its surface attachment. Strong anchoring of PPO blocks has been a feature observed in explicit molecular simulations of the adsorption of Pluronics to CNTs. , …”
Section: Resultsmentioning
confidence: 96%
“…Therefore, several dispersion methodologies have been devised, particularly in water. , Among those methodologies, the physical adsorption of dispersant molecules on the nanotube surface is often preferred because it (in contrast to chemical functionalization ) preserves the chemical and structural integrity of the nanotube. Thus far, several types of dispersantsusually amphiphilic molecules such as surfactants, synthetic polymers, proteins, and DNA have been used to exfoliate and stabilize CNTs in aqueous solvents. The adsorption of these dispersants onto the CNT surface is mainly driven by hydrophobic interactions , or π-stacking. , Further, electrostatic and/or steric repulsions between the surface-covered nanotubes provide the necessary kinetic stability of the obtained colloidal dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Aslan et al compares density profiles of PEGylated lipids adsorbed onto isolated and bundled CNTs, which helps explain their different extents of antimicrobial activity [205]. Sarukhanyan et al [206] and Han et al [207] simulated CNTs interacting with various polymers, showing the effect of polymer hydrophobicity on the CNT-polymer conformation and interparticle dispersion. Maatta et al found the dependence of CNT dispersion on PEG length and CNT diameter [208].…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…On the other hand, solvent polarity was shown to affect polymer adsorption on CNTs by altering polymer flexibility and the strength of nonbonded interactions [14]. MD simulations also provided important details on the interaction between CNTs and various polymeric systems, such as pyrene-attached polyethylene chains [14], branched PPOpolyethylene oxide segments [15], different polyether surfactants [16], polyamide-66 [17], lipid-PEG chains [18], and different flexible polymers [19,20].…”
Section: Introductionmentioning
confidence: 99%